2011
DOI: 10.1007/s12310-011-9056-7
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Teachers in School-Based Suicide Prevention: A Qualitative Study of School Staff Perspectives

Abstract: In response to concerns over youth suicide, there has been an increase in school-based suicide prevention programs. However, we know little about teacher perspectives on school-based suicide prevention and mental health programs. This study examined teacher roles in the implementation of a district-wide suicide prevention program through focus groups and interviews with middle school teachers, administrators, and other school personnel. Study results highlighted teachers’ critical role in detecting students at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 33 publications
(40 reference statements)
3
32
0
Order By: Relevance
“…In a qualitative study of a large (approximately 900 schools) districtwide school gatekeeper training program, Nadeem et al. () concluded that school teachers may feel overburdened, isolated, and incompetent in their roles as gatekeepers if the schools were high need or had very limited resources. Moreover, as part of a large and rigorous evaluation of school‐based gatekeeper training, Wyman, Henry, Knoblauch, and Brown () observed that referrals of suicidal youth actually declined following implementation of the program and did not begin to increase again until approximately 20% of school staff had been trained.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a qualitative study of a large (approximately 900 schools) districtwide school gatekeeper training program, Nadeem et al. () concluded that school teachers may feel overburdened, isolated, and incompetent in their roles as gatekeepers if the schools were high need or had very limited resources. Moreover, as part of a large and rigorous evaluation of school‐based gatekeeper training, Wyman, Henry, Knoblauch, and Brown () observed that referrals of suicidal youth actually declined following implementation of the program and did not begin to increase again until approximately 20% of school staff had been trained.…”
Section: Resultsmentioning
confidence: 99%
“…In their qualitative study, Nadeem et al. () concluded that the presence of adverse consequences associated with school‐based (K‐12) gatekeeper trainings may be dependent upon the quality of crisis policies and procedures, collaboration among staff, and the presence of mental health professionals or counselors on school campuses. Bean and Baber () reached similar conclusions in their evaluation of Project Connect, a community‐based suicide prevention program using gatekeeper training.…”
Section: Resultsmentioning
confidence: 99%
“…This study is part of a broader examination of the implementation of YSPP in one of the nation's largest school districts serving approximately 688,000 students, predominantly low‐income (77% qualify for free/reduced‐cost lunch) and from racial/ethnic minority backgrounds (about 73% Latino, 11% Black, 6% Asian/Pacific Islander). We categorized district middle schools (N = 80) as having high, middle, or low YSPP implementation, by the number of suicide risk assessment forms completed per enrolled student per year, and 6 schools were randomly sampled from the high and low categories (3 in each category).…”
Section: Methodsmentioning
confidence: 99%
“…Each school had a predominantly minority population, primarily Latino, with 33‐56% of students being English language learners and an average class size of 28 to 32 students. Additional school characteristics are reported elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…The importance of being able to refer directly within a school context has been demonstrated (Freedenthal & Breslin 2010;Nadeem, Kataoka, Chang, Vona, Wong & Stein 2011;Westefield et al 2007). Whereas in a study of health education teachers only a quarter felt that if they talked to parents it would reduce the risk of suicide (27%) (King et al 1999).…”
Section: Introductionmentioning
confidence: 99%